Examining the issues of conventional and islamic trust receipt in banks - Syed Alwi, Sharifah Faigah; Osman, Ismah; Mohammad Hatta, Mohammad Firdaus; Ibrahim, Uzaimah; Sawari, Mohd Fuad (American Scientific Publishers, 2015)
One of the conventional trade finance facilities is trust receipt. This facility is known as Murabahah Trust Receipt-i (TR-i) in Malaysian Islamic banks. The objective of this paper is to examine the nature of both conventional and Islamic trust receipt in terms of the similarities and differences. The second objective is to ascertain the application of the trust receipt in Murabahah TR-i. Lastly, to determine whether, the use of letter of hypothecation both in conventional and Murabahah TR-i conforms to Shariah requirements. The qualitative method is adopted, where the information on the practices of eleven Islamic banks in Malaysia is gained through semi-structured interviews conducted with the bankers who are directly involved with Murabahah TR-i. Apparently, this paper discovered that the nature of conventional and Islamic trust receipt is totally different. Thus, it is not appropriate for Islamic banks to use the term trust receipt for their Murabahah TR-i facility. Additionally, it is found that the usage of letter of hypothecation in Murabahah TR-i facility is not required in Murabahah (mark-up) contract. Eventually, Bank Negara Malaysia’s role is very crucial in determining the appropriateness of using the trust receipt facility in Islamic banks and the letter of hypothecation in Murabahah TR-i for Islamic banks.